2016
DOI: 10.11648/j.ijnfs.20160503.18
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Iron, Zinc, Vitamin E and Vitamin C Supplementation on Thyroid Hormones in Rats with Hypothyroidism

Abstract: Abstract:The aim of the study was to investigate the effect of Iron, Zinc, Vitamin C (Vit.C) and Vitamin E (Vit.E) supplementation on thyroid hormones in rats with hypothyroidism. Thirty six rats were divided into two main groups, the first main group (6 rats) was fed on basal diet only. The second main group (30 rat) were injected with 10 mg/kg/day Propylthiouracil (PTU) to induce hypothyroidism, was divided into 5 subgroups: including control positive group that fed on basal diet, and the other subgroups wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 77 publications
0
10
0
3
Order By: Relevance
“…The best thyroid functions were observed in rats fed on MOO compared to the other treated groups. The results of Rabeh and El-Ghandour (2016) and Rabeh (2017) indicated that thyroid hormones were dramatically reduced by PTU. Bhanja and Chainy (2010) reported that hypothyroidism causes oxidative stress in rats.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The best thyroid functions were observed in rats fed on MOO compared to the other treated groups. The results of Rabeh and El-Ghandour (2016) and Rabeh (2017) indicated that thyroid hormones were dramatically reduced by PTU. Bhanja and Chainy (2010) reported that hypothyroidism causes oxidative stress in rats.…”
Section: Resultsmentioning
confidence: 97%
“…According to Siddalingaswamy et al (2011) and Pretha et al (2013), VCO ables to positively influence liver functions. Rabeh and El-Ghandour (2016) and Aisuodionoe et al (2018) reported that VCO improves metabolic parameters, antioxidant enzyme activities, reduces oxidative stress and lipid peroxidation in diabetes. Famurewa et al (2018) mentioned that beneficial effects of VCO on lipid profile, antioxidant hepatic defense system, and cardiovascular risk indices in rats.…”
Section: Resultsmentioning
confidence: 99%
“…The level of serum glucose increased significantly (p≤0.05) in PC group (STZ-treated); and reduced significantly (p≤0.05) in CUR (100 & 200 mg/kg b.w) and CUR coupled with ZnCl 2 (15 mg/kg b.w) treated groups, concerning the PC. Histopathological investigations revealed that the diabetic liver had a high degree of hydropic degeneration accompanied by coagulative necrosis (Figure 2 Our study provided an advanced model and more information concerning using treatment mixtures and important measurements for the provided model of diabetes [32]. Oxidative stress plays an important role in the pathogenesis and etiology of diabetes [33].…”
Section: Resultsmentioning
confidence: 98%
“…47 O Zn tem um lugar importante entre os micronutrientes necessários para o metabolismo da tireoide, além do Se e do iodo. 48 Um estudo 49 mostrou que a deficiência de Zn está associada à diminuição dos níveis de secreção de hormônios da tireoide, afetando o metabolismo do corpo e a taxa metabólica de repouso. 48 Na conversão periférica de T 4 a T 3 regulada pelas deiodinases tipo I e II, a primeira é uma enzima dependente de Se, e é possível que a deiodinase tipo II seja uma proteína dependente de Zn, ou, então, que necessite desse mineral como cofator no processo de deiodinação.…”
Section: Gestantesunclassified
“…48 Um estudo 49 mostrou que a deficiência de Zn está associada à diminuição dos níveis de secreção de hormônios da tireoide, afetando o metabolismo do corpo e a taxa metabólica de repouso. 48 Na conversão periférica de T 4 a T 3 regulada pelas deiodinases tipo I e II, a primeira é uma enzima dependente de Se, e é possível que a deiodinase tipo II seja uma proteína dependente de Zn, ou, então, que necessite desse mineral como cofator no processo de deiodinação. 50 O Zn ainda parece ser necessário para o receptor da T 3 adotar sua confirmação biologicamente ativa.…”
Section: Gestantesunclassified